First-Generation College Students as Academic Learners: A Systematic Review. (April 2020) - Ives, Jillian; Castillo-Montoya, Milagros
The literature on first-generation college students largely focuses on the challenges and barriers they may experience in college. Yet, we do not have a clear understanding of who these students are as learners. To address this gap, this systematic review examines how scholars study and conceptualize first-generation college students as learners. We found the majority of the literature we reviewed conceptualized them as learners based on their academic performance and the influence of cultures on their learning. These two conceptualizations positioned first-generation college students against normative ways of learning, and in doing so promulgate an assimilation approach in higher education. We found a smaller body of literature that conceptualized first-generation college students as learners whose lived experiences, when connected to academic content, can contribute to their academic learning, advancement of disciplines, self-growth, and community development. We use this alternative view to provide recommendations for studying and working with first-generation college students.